Oxidative Formation and Removal of Complexed Mn(III) by Pseudomonas Species - Wright, Mitchell H.; Geszvain, Kati; Oldham, Véronique E.; Luther, George W.; Tebo, Bradley M. (Frontiers in Microbiology, 2018)
The observation of significant concentrations of soluble Mn(III) complexes in oxic, suboxic and some anoxic waters has triggered a re-evaluation of the previous Mn paradigm; which focused on the cycling between soluble Mn(II) and insoluble Mn(III,IV) species as operationally defined by filtration. Though Mn(II) oxidation in aquatic environments is primarily bacterially-mediated, little is known about the effect of Mn(III)-binding ligands on Mn(II) oxidation nor on the formation and removal of Mn(III). Pseudomonas putida GB-1 is one of the most extensively investigated of all Mn(II) oxidizing bacteria, encoding genes for three Mn oxidases (McoA, MnxG and MopA). P. putida GB-1 and associated Mn oxidase mutants were tested alongside environmental isolates Pseudomonas hunanensis GSL-007 and Pseudomonas sp. GSL-010 for their ability to both directly oxidize weakly and strongly bound Mn(III), and to form these complexes through the oxidation of Mn(II). Using Mn(III)-citrate (weak complex) and Mn(III)-DFOB (strong complex), it was observed that P. putida GB-1, P. hunanensis GSL-007 and Pseudomonas sp. GSL-010 and mutants expressing only MnxG and McoA were able to directly oxidize both species at varying levels; however, no oxidation was detected in cultures of a P. putida mutant expressing only MopA. During cultivation in the presence of Mn(II) and citrate or DFOB, P. putida GB-1, P. hunanensis GSL-007 and Pseudomonas sp. GSL-010 formed Mn(III) complexes transiently as an intermediate before forming Mn(III/IV) oxides with the overall rates and extents of Mn(III,IV) oxide formation being greater for Mn(III)-citrate than for Mn(III)-DFOB. These data highlight the role of bacteria in the oxidative portion of the Mn cycle and suggest that the oxidation of strong Mn(III) complexes can occur through enzymatic mechanisms involving multicopper oxidases. The results support the observations from field studies and further emphasize the complexity of the geochemical cycling of manganese.